Inside Back Cover: Highly Luminescent π‐Conjugated Terpyridine Derivatives Exhibiting Thermally Activated Delayed Fluorescence (Chem. Eur. J. 1/2017). Issue 1 (10th November 2016) - Sasabe, Hisahiro; Hayasaka, Yuya; Komatsu, Ryutaro; Nakao, Kohei; Kido, Junji
Abstract : A series of terpyridine/acridine conjugates exhibits strong blue‐to‐green emission and thermally activated delayed fluorescence (TADF) character in the solid state. An organic light‐emitting device with a green emissive terpyridine/acridine conjugate showed an external quantum efficiency of approximately 25%, a power efficiency of over 80 lm W −1, and an exceptionally low‐efficiency roll‐off. More information can be found in the Full Paper by H. Sasabe and J. Kido et al. onpage 114 ff.